Dimensions of Coach Work Passion and Sportsman Performance: An Empirical Study on Psychological Attributes of Athletes in China - Xiaofang Yang, Bo DaI, Yidong Miao (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
In recent years, the value of sports and other physical activities has increased considerably and the role of the coaches of sportsmen is essential in providing trainings to sportsmen to help them achieve their objectives and improve their performance. The purpose of this study is to understand the passion of sports coaches for their China with the aim of knowing which type of passions yield good performance among sportsmen. For this reason, the study seeks to study the Coaches’ work passion in which harmonious and obsessive work passion was included, and to see its impact on performance of the sportsmen with mediating role of psychological empowerment. To achieve the objectives of this study, quantitative study was carried out in which questionnaires were filled out by respondents including coaches, trainers and sportsmen. After analyzing the questionnaires, it was revealed that there is significant and positive impact of harmonious work passion on the performance of the sportsmen, while in the case of obsessive work passion, the results showed that there is significant and a negative relation of obsessive work passion with the performance of sportsmen. This study contains both theoretical and practical insights that can help stakeholders in the sports sector determine how desired results (in terms of performance) can be obtained from the coaches’ work passion.